Carbon microtube aerogel derived from kapok fiber : an efficient and recyclable sorbent for oils and organic solvents - Song, Pin (2022)
A carbon microtube aerogel (CMA) with hydrophobicity, strong adsorption capacity, and superb recyclability was obtained by a feasible approach with economical raw material, such as kapok fiber. The CMA possesses a great adsorption capacity of 78-348 times its weight. Attributed to its outstanding thermal stability and excellent mechanical properties, the CMA can be used for many cycles of distillation, squeezing, and combustion without degradation, which suggests a potential practical application in oil-water separation. In addition, the adsorption capacity still retained 98% by distillation, 97% by squeezing, and 90% by combustion after 10 cycles. Therefore, the obtained CMA has a broad prospect as an economical, efficient, and environmentally friendly adsorbent.